A rare case report of cornual pregnancy - Bansal, Priyanka; Aggarwal, Gargi; Bansal, Isha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Cornual pregnancy is a rare type of ectopic pregnancy in which embryo implants in the junction between the fallopian tube and uterus. Ectopic pregnancy is more common in the ampullary region of the fallopian tube. However, cornual (interstitial) pregnancy is seen in 2-4% of ectopic pregnancies. It is more dangerous than other ectopic as it may lead to catastrophic hemorrhage, shock with mortality rate of 2-2.5%. A cornual pregnancy is diagnosed at 7+3 week of amenorrhea in 27-year-old healthy woman. Ultrasound examination showed a right live cornual pregnancy with CRL corresponding to 6+4week of gestation with fetal heart pulsation. We performed right cornuostomy by laparotomy without any immediate or delayed postoperative complications. Cornual pregnancy poses significant diagnostic and therapeutic challenge; early diagnosis may help to select the proper management and treatment according to the clinical presentation, hemodynamic stability, serum b-hCG level and ultrasound findings. Early diagnosis and management remain the mainstay for tackling maternal mortality due to cornual pregnancy.